Epistaxis and atorvastatin: is there an association and are clinicians aware? A retrospective audit of 100 patients. Issue 2 (22nd February 2020) - Heward, E; Lau, A S
Abstract: Objective: Epistaxis is a common ENT presentation. The British National Formulary lists epistaxis as a common side effect of atorvastatin. This study aimed to better understand the relationship between epistaxis and atorvastatin use, and determine whether ENT doctors are aware of its side effect profile. Methods: A retrospective analysis over 10 months identified 100 individuals who presented to hospital with epistaxis. A questionnaire of 24 ENT registrars was undertaken. Results: Of the 100 patients admitted with epistaxis, 27 were receiving atorvastatin and 21 simvastatin. None of the 24 ENT registrars were aware that epistaxis was a listed common side effect of atorvastatin. Conclusion: There was no apparent difference in the proportion of patients admitted with epistaxis taking atorvastatin versus simvastatin. Epistaxis is an unknown side effect of atorvastatin; doctors have an obligation to be aware of the pharmaceutical literature and to consider alternatives, particularly in re-admissions cases.